2020
DOI: 10.3389/fimmu.2020.00943
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Nephropathy: Perspective on Extracellular Vesicles

Abstract: Diabetic nephropathy (DN) is a major microvascular complication of diabetes mellitus. It is the most frequent cause of end-stage renal disease with no definitive therapy available so far. Extracellular vesicles (EVs), including exosomes, microvesicles, and apoptotic bodies, are nano-and micron-sized heterogeneous vesicles that can be secreted by almost all cell types. Importantly, EVs contain many biologically active materials, such as RNAs, DNAs, proteins, and lipids, from their parental cells, which can be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 65 publications
(62 reference statements)
0
62
0
1
Order By: Relevance
“…However, in renal and metabolic diseases, urine stands out as a sound alternative for EV studies [ 12 , 36 ]. First, urine collection is noninvasive, fast and easy, and second, it has been postulated that uEVs, coming from all parts of the nephrons and collecting ducts, might mainly be of renal origin, since circulating EVs are not able to pass through the glomerular membrane, at least in physiological conditions [ 10 ]. Therefore, the study of uEV content and distribution might give insights into the physiopathology of DKD, and contribute to the discovery of novel early diagnosis and risk stratification biomarkers, as well as therapeutic targets in this pathology.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in renal and metabolic diseases, urine stands out as a sound alternative for EV studies [ 12 , 36 ]. First, urine collection is noninvasive, fast and easy, and second, it has been postulated that uEVs, coming from all parts of the nephrons and collecting ducts, might mainly be of renal origin, since circulating EVs are not able to pass through the glomerular membrane, at least in physiological conditions [ 10 ]. Therefore, the study of uEV content and distribution might give insights into the physiopathology of DKD, and contribute to the discovery of novel early diagnosis and risk stratification biomarkers, as well as therapeutic targets in this pathology.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…The lack of sensitivity and specificity of albumin for the early identification of high-risk patients has prompted the search for novel noninvasive alternatives to cover this clinical need. EVs, and more precisely uEVs, have emerged as a plausible option in this regard, since the structure of the glomerular membrane, at least in healthy condition, restrains the passage of circulating EVs to urine, and thus uEVs derived from all parts of the nephrons and collecting ducts might be mainly of renal origin [ 10 ]. Likewise, the determination of the total uEV numbers or specific uEV subpopulations, and the analysis of their content might help to identify novel biomarkers and therapeutic targets for DKD risk assessment in every segment of the nephron, serving as early biomarkers of renal dysfunction and structural injury ( Table 2 ).…”
Section: Urinary Extracellular Vesicles (Uevs) As Potential Biomarkers In Diabetic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the predictive value for the development of DKD is proven for a number of miRNA types, mRNA (mainly for the Wilms tumour protein 1 [WT1 protein], which plays a major regulatory role in podocyte homeostasis) and proteins (e.g. megalin C, WT1 protein itself, regucalcin, osteoprotegerin, aquaporins 2 and 5, and others) and the constellations of these components, enclosed inside the MV [47,48].…”
Section: Extracellular Vesicles -A New Category Of Biomarkers In Dkdmentioning
confidence: 99%
“…Diabetic nephropathy is the main cause of end-stage renal disease, and its major pathologic feature is renal fibrosis [8]. Many studies have indicated that lncRNAs participate in the pathogenesis and progression of diabetic nephropathy [9].…”
Section: Introductionmentioning
confidence: 99%